Altering the calcium-phosphorus ratio for fattening steers - Wilkes, Roy Philip, author; Washburn, L. E., advisor; Henney, Homer J., committee member; Cross, Floyd, committee member; Frey, Paul Reheard, committee member; Tom, R. C., committee member (Colorado State University. Libraries, 1943)
To view the abstract, please see the full text of the document.
Keywords: Feeds; Cattle